Atención de enfermería en mujeres embarazadas con infecciones de vías urinarias, hospitalizadas en la Unidad Médica del IESS Babahoyo periodo 2012 - García Mora, María Fernnda (2013)
Urinary tract infections , is one of the most common medical complications in pregnancy, making it a health problem, the physiological changes associated with pregnancy predispose to complications that can significantly affect the mother and the fetus. Regardless of geographic and economic situation. The ministry of public health tools to implement better care of the pregnant patient, it began to be used in all health institutions in which quality most appropriate care for the population of the country was provided. The pregnant woman should undergo monthly checks their status , to check the condition of the product of pregnancy and growth and development are appropriate, in addition to investigating whether diseases exist in the mother and her fetus , which can lead to high morbidity and mortality. This research will take place at the hospital IESS Babahoyo to determine how these factors affect nursing care in the recovery of patients with urinary tract infections in hospitalized medical unit eta as it is the leading cause of birth Threat preterm . This work will be very important because thanks to it we can identify strengths and weaknesses in the care provided by the nursing staff in preventing early diagnosis and timely treatment. People which will benefit will be the users of that institution since knowing the quality of care provided to hospitalized pregnant patients , they were correct or improve care for pregnant women in their prenatal stage, and in turn their children . In the ward , we can observe the increase of pregnant women who were seeking care from health care , lack of knowledge about the self that must carry in their pregnancy , involves a self-infection can occur when when cleaning the genitals. The relationship between urinary tract infection , preterm birth and low birth weight has been well documented . About 27 % of preterm births have been associated with some type of urinary tract infection . The objective of the research is to determine how these factors affect nursing care in the treatment and recovery of pregnant women with urinary tract infections , who were hospitalized in the medical unit Babahoyo IESS 2012 period . The hypothesis for this study is as follows If quality care is provided pregnant women with urinary tract infections attending the hospital IESS Babahoyo guarantee a good result at term? The main conclusions Of the total number of users who came to the hospital IESS in gestation during the period of 2012 , we obtained 124 patients with severe urinary tract infection , we indicating this figure a number with this infection . Infection occurred more frequently in women between the ages of 26 to 35 years followed by 15 to 25 years due to lack of knowledge and inexperience . The early detection and treatment of UTI in pregnant should be a priority to safeguard the life of the mother and the unborn baby . And we end with recommendations : We feel the responsibility to develop a proposal which aims in terms of promotion and prevention measures on urinary tract infection and healthy pregnancy , with emphasis on self-care, for the benefit of pregnant women . We suggest that the authorities take into account the professional not only deepened their knowledge regarding other issues , but also to provide information on urinary tract infection because most pregnant women do not have a clear understanding on what regarding this issue , so it can avoid recurrent urinary tract infections and so therefore complications in pregnancy. We also propose that related information is given to healthy pregnancy , only then can decrease the incidence of urinary tract infections . Regarding the results of recent research and knowledge held as future nursing professionals should emphasize the importance of prevention and self-care for urinary tract infections , where not only is drunk to have not only the preventive measures but also future complications in the population . They continue to provide educational programs and conducting the implementation of the post queries pregnant . Emphasize performed urine culture for pregnant women, because through this you can know which type of bacteria causing the infection and appropriate treatment owed to offer.